Coiling Versus Microsurgical Clipping in the Treatment of Unruptured Middle Cerebral Artery Aneurysms: A Meta-Analysis. Issue 5 (9th February 2018) - Alreshidi, Meshal; Cote, David J; Dasenbrock, Hormuzdiyar H; Acosta, Michael; Can, Anil; Doucette, Joanne; Simjian, Thomas; Hulou, M Maher; Wheeler, Lee A; Huang, Kevin; Zaidi, Hasan A; Du, Rose; et al.
Abstract: BACKGROUND: Open microsurgical clipping of unruptured intracranial aneurysms has long been the gold standard, yet advancements in endovascular coiling techniques have begun to challenge the status quo. OBJECTIVE: To compare endovascular coiling with microsurgical clipping among adults with unruptured middle cerebral artery aneurysms (MCAA) by conducting a meta-analysis. METHODS: A systematic search was conducted from January 2011 to October 2015 to update a previous meta-analysis. All studies that reported unruptured MCAA in adults treated by microsurgical clipping or endovascular coiling were included and cumulatively analyzed. RESULTS: Thirty-seven studies including 3352 patients were included. Using the random-effects model, pooled analysis of 11 studies of microsurgical clipping (626 aneurysms) revealed complete aneurysmal obliteration in 94.2% of cases (95% confidence interval [CI] 87.6%-97.4%). The analysis of 18 studies of endovascular coiling (759 aneurysms) revealed complete obliteration in 53.2% of cases (95% CI: 45.0%-61.1%). Among clipping studies, 22 assessed neurological outcomes (2404 aneurysms), with favorable outcomes in 97.9% (95% CI: 96.8%-98.6%). Among coiling studies, 22 examined neurological outcomes (826 aneurysms), with favorable outcomes in 95.1% (95% CI: 93.1%-96.5%). Results using the fixed-effect models were not materially different. CONCLUSION: This updated meta-analysis demonstrates that surgical clipping for unruptured MCAA remains highly safe and efficacious. Endovascular treatment for unruptured MCAAs continues to improve in efficacy and safety; yet, it results in lower rates of occlusion.